[Pt(O,O′-acac)(γ-acac)(DMS)], a new Pt compound exerting fast cytotoxicity in MCF-7 breast cancer cells via the mitochondrial apoptotic pathway - Muscella, A (Nature Publishing Group, 2007)
BACKGROUND AND PURPOSE: We showed previously that a new Pt complex containing an O,O′-chelated acetylacetonate ligand (acac) and a dimethylsulphide in the Pt coordination sphere, [Pt(O,O′-acac)(γ-acac)(DMS)], induces apoptosis in HeLa cells. The objective of this study was to investigate the hypothesis that [Pt(O,O′-acac)(γ-acac)(DMS)] is also cytotoxic in a MCF-7 breast cancer cell line relatively insensitive to cisplatin, and to gain a more detailed analysis of the cell death pathways. EXPERIMENTAL APPROACH: Cells were treated with Pt compounds and cytotoxicity tests were performed, together with Western blotting of various proteins involved in apoptosis. The mitochondrial membrane potential was assessed by fluorescence microscopy and spectrofluorometry and the Pt bound to cell fractions was measured by atomic absorption spectrometry. KEY RESULTS: In contrast to cisplatin, the cytotoxicity of [Pt(O,O′-acac)(γ-acac)(DMS)] correlated with cellular accumulation but not with DNA binding. Also, the Pt content in DNA bases was considerably higher for cisplatin than for [Pt(O,O′-acac)(γ-acac)(DMS)], thus excluding DNA as a target of [Pt(O,O′-acac)(γ-acac)(DMS)]. [Pt(O,O′-acac)(γ-acac)(DMS)] exerted high and fast apoptotic processes in MCF-7 cells since it provoked: (a) mitochondria depolarization; (b) cytochrome c accumulation in the cytosol; (c) translocation of Bax and truncated-Bid from cytosol to mitochondria and decreased expression of Bcl-2; (d) cleavage of caspases -7 and -9, and PARP degradation; (e) chromatin condensation and DNA fragmentation. CONCLUSIONS AND IMPLICATIONS: [Pt(O,O′-acac)(γ-acac)(DMS)] is highly cytotoxic for MCF-7 cells, cells relatively resistant to many chemotherapeutic agents, as it activates the mitochondrial apoptotic pathway. Hence, [Pt(O,O′-acac)(γ-acac)(DMS)] has the potential to provide us with new opportunities for therapeutic intervention.